Ibn Sina’ s Concept of Wajib al-Wujud - Hamid Fahmy Zarkasyi (TSAQAFAH, 2011)
This paper is an exposition of Ibn Sina’ s concept  Wa> jib al-W uju> d(Necessary Existence),a concept of God derived from or modified out of   Aristotle’ s natural theology .Since it deviates from  Aristotle’ s philosophy ,it considerably distinct from the Greek philosophical tradition. Unlike Aristotle whose theological framework departs from physic, Ibn Sina delineates the concept of God from pure metaphysical approach consisting of ontological and cosmological arguments.From this delineation Ibn Sina has successfully solved  Aristotle’ s problem of God knowledge and change, and that is by positing that God knew something other than Himself but it does not imply change in His essence since His knowledge is unbounded by time.Be that as it ma y ,this philosophical concept is subject to further examination from theological perspectives .However,the term Wa> jib al-W uju> d is a key concept for the explication of the existence of God, but the term itself is not assumption,but the goal to be investigated.  Although Necessary Existence is only ontological concept it is used in his various way of proving God’ s existence,whether in cosmological argument or other argument. Interestingly ,since all depend on the key concept of   ‘necessity’,the proof that begins from the causality does not end in the First Cause but on Wajib al-W ujud, an end that seems to be incompatible with the beginning .